Variação geográfica em Caluromys philander (Linnaeus, 1758) no Brasil (Didelphimorphia: Didelphidae) - Caramaschi, Fabiana Pellegrini (2005)
Caluromys philander is an arboreal marsupial widely distributed in Brazil. Three subspecies are currently recognized, despite the lack of comprehensive analyses of geographical variation. This study aimed 1) to map the distribution of C. philander in Brazil, 2) to evaluate the existence of secondary sexual dimorphism in craniometric characters in the species, 3) to analyze the cranial and pelage variability among samples representing the distribution of this taxon in Brazil, and 4) to review the taxonomy of Caluromys philander in the light of the contrast between the morphometric patterns and the results of molecular analyzes already available. Localities were grouped into regional groups on the basis of geographic distances. Secondary sexual dimorphism was only detected when a high statistical power was possible. Big samples (with more than ten specimens) were used in confirmatory multivariate analyses providing a pattern of geographic differentiation that was common between analyzes of each sex and of pooled sexes. This pattern, which has differentiated the sample from southeastern Brazil, has also been revealed in the analysis of qualitative cranial characters, specifically the interorbital and post-orbital breadths; shape of the lacrimal bone, and of the coronoid process. These results, together with independent molecular analyzes, are interpreted here as evidence that the form from southeastern – south of Brazil does constitute a distinct species, for which the name Caluromys dichrurus (Wagner, 1842) is available.